Composition and bioactivities of the rhizomes essential oil of curcuma aeruginosa / Nor Akmalazura Jani ...[et al.] - Jani, Nor Akmalazura; Rokman, Farah Aina; Iberahim, Rashidah; Khamis, Shamsul (Universiti Teknologi MARA Cawangan Pahang, 2021)
Curcuma aeruginosa is a perennial tropical herb that belongs to the Zingiberaceae family. The essential oil composition as well as antibacterial and antioxidant activities of the rhizomes of C. aeruginosa growing from Kluang, Johor, Malaysia were investigated. Extraction of the essential oil was conducted using the hydrodistillation technique and the chemical composition was established using gas chromatography-mass spectrometry (GC-MS). The antibacterial activity against four bacteria strains (Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Salmonella typhi) was determined using a disc diffusion method, while the antioxidant activity was tested using 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging method. The rhizomes of C. aeruginosa afforded 0.07% w/w of pure essential oil, of which 35 volatile compounds, accounting for 84.9% were successfully identified. Curzerenone (33.8%), 1,8-cineole (13.5%), and camphor (6.7%) were found as the predominant compounds in the oil. Bioactivity studies on the oil revealed that the oil demonstrated an antibacterial effect against all tested bacteria with the biggest diameter of inhibition was towards B. cereus (10.00 mm). However, no antioxidant activity was observed by the rhizomes essential oil of C. aeruginosa.